Use of the Internet of Things (IoT) in the Context of Ubiquitous Learning in Higher Education - Rini Nuraini; Baharuddin Baharuddin; Daniar Sofeny; Mariana Diah Pusitasari; Victor Benny Alexsius Pardosi (Journal of Social Science Utilizing Technology, 2024)
Background. The use of the Internet of Things (IoT) in Ubiquitous Learning in higher education is increasingly important along with the development of 21st century internet technology. Reliance on the internet for information creates a new paradigm in learning, where IoT plays a key role supporting an equitable and integrated learning experience. Universities as centers of higher education need to adopt solutions using IoT technology to overcome problems in the context of Ubiquitous Learning. Purpose. The purpose of this research is to identify solutions that can be adopted by universities to overcome Internet of Things problems in the context of Ubiquitous Learning. Method. This research uses a quantitative methodology with a survey method approach. A total of 30 students were randomly selected as samples to provide adequate representation. The data analysis technique uses the Miles Huberman technique, involving the stages of data reduction, data presentation, and drawing conclusions. A questionnaire was developed to explore students’ perceptions and experiences regarding the use of IoT in the learning process. Results. From the analysis results, the majority of students show a good understanding of IoT concepts and are actively involved in learning using this technology. Although some face obstacles, the majority of respondents believe that the use of IoT can increase learning effectiveness and really hope that there will be increased student engagement through IoT technology. These results provide a strong basis for developing better implementation strategies, encouraging universities to continue to innovate in integrating IoT technology to improve student learning experiences in the future.   Conclusion. Universities are advised to continue to innovate, integrating IoT strategically to improve the student learning experience. This shows the significant impact of IoT in designing the future of learning in higher education.